The Effect of Side Effects Tuberculosis Treatment in the Early Stage Towards Compliance with Tuberculosis Patients - Joko Sapto Pramono; Nilam Noorma; Andi Lis Arming Gandini; Sopia Fitriani (Health Notions, 2021)
Pulmonary tuberculosis treatment causes various side effects including nausea and vomiting, itching, vision problems, and anemia. Drug side effects in the early stages are one of the causes of non-adherence to complete treatment. The purpose of this study was to analyze the effect of the side effects Tuberculosis treatment in the early stages on treatment compliance for tuberculosis patients. This study used a cross sectional design. Samples were taken as many as 71 respondents, the instruments used were side effects of early-stage tuberculosis treatment and compliance with tuberculosis treatment in tuberculosis patients from the Morisky Medication Adherence Scale (MMAS). The results of the study found 97.7% adherent and 2.3% non-adherent, 39.5% mild side effects and 60.5% severe side effects. Chi-square test showed that no significant difference between the side effects of TB treatment in the early stages of tuberculosis treatment compliance in patients p = 0.669 at significant level of 95% (α = 0.05). There was no effect between the side effects of Tuberculosis treatment in the early stages of treatment compliance for Tuberculosis patients. It was recommended that health workers continue to monitor the side effects of tuberculosis treatment and provide motivation to carry out treatment completely. Keywords: side effects; early stage; treatment; pulmonary tuberculosis; compliance